2014
DOI: 10.1111/1365-2435.12376
|View full text |Cite
|
Sign up to set email alerts
|

Bacteria and the evolution of honest signals. The case of ornamental throat feathers in spotless starlings

Abstract: Summary1. Mechanisms guaranteeing reliability of messages are essential in understanding the underlying information and evolution of signals. Micro-organisms may degrade signalling traits and therefore influence the transmitted information and evolution of these characters. The role of micro-organisms in animal signalling has, however, rarely been investigated. 2. Here, we explore a possible role for feather-degrading bacteria driving the design of ornamental throat feathers in male spotless starlings (Sturnus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 52 publications
2
28
1
1
Order By: Relevance
“…Previous studies of other birds found a positive relationship between uropygial gland size and amount of secretion produced (Martín-Vivaldi et al 2009;Ruiz-Rodríguez et al 2015). We also found a positive association between gland height and volume of secretion, but only for swallows captured in contaminated areas in Ukraine, which might be related to the relatively higher selection pressures at these locations (see above).…”
Section: Uropygial Secretionsupporting
confidence: 55%
See 2 more Smart Citations
“…Previous studies of other birds found a positive relationship between uropygial gland size and amount of secretion produced (Martín-Vivaldi et al 2009;Ruiz-Rodríguez et al 2015). We also found a positive association between gland height and volume of secretion, but only for swallows captured in contaminated areas in Ukraine, which might be related to the relatively higher selection pressures at these locations (see above).…”
Section: Uropygial Secretionsupporting
confidence: 55%
“…Although the antimicrobial activity of uropygial secretions is an ongoing topic of discussion in the literature, several studies have found antimicrobial components in uropygial secretion (Martín-Platero et al 2006;Martín-Vivaldi et al 2010;Ruiz-Rodríguez et al 2013) and direct evidence of inhibition of bacterial growth (Shawkey et al 2003;Ruiz-Rodríguez et al 2015), including feather-degrading bacteria (Møller et al 2009). However, other studies have failed to detect antimicrobial properties of secretion (Giraudau et al 2013;Reneerkens et al 2008).…”
Section: Uropygial Secretionmentioning
confidence: 99%
See 1 more Smart Citation
“…We suggest that a possible link here would involve physiological pathways that increase resistance of wing feathers to abrasion. For instance, resistance to feather‐degrading bacteria and ectoparasites is likely to be mediated by uropygial gland functioning (reviewed by Ruiz‐Rodríguez et al ). This gland produces waxes, sterols and hydrocarbons that are important to maintain the plumage supple, rigid and to protect it against abrasion (Jacob and Ziswiler , Shawkey et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it has recently started to be subject of in-depth research from an ecological and evolutionary framework (e.g., [17,18]). Regarding interactions between bacteria and birds, it has been shown that different types of bacteria interact with nestling growth [19,20], may increase adult predation rates [21], and may be involved for instance in the evolution of uropygial glands [22], plumage colouration or maintenance [23][24][25], nest material composition [26,27], incubation behaviours [28,29], or even cognitive skills of birds [30]. Because of the important and diverse roles that bacteria may play in the ecology and evolution of life histories and behaviour in higher organisms (reviewed in [31][32][33][34]), detecting a causal link between ectoparasitism and bacterial infections would contribute to the understanding of parasite-host interactions.…”
Section: Introductionmentioning
confidence: 99%